زيارة الأربعين المشروعية والأبعاد - القريشى، فالح حسن على (العتبة الحسينية المقدسة - مركز كربلاء للدراسات والبحوث, 2022)
تحتل الزيارات والأماكن المقدسة موقعا هاما في شخصية الإنسان المتدين في كل الديانات وتأثيرها لا يقتصر على الواجبات، بل يمتد ليشمل المستحبات والمكروهات التي تترك آثارا إيجابية على وعي الإنسان وسلوكه وتفكيره. ولذلك فإن زيارة العتبات المقدسة والمستحبات الأخرى تترك روابط عميقة وأثرا بالغا في ترسيخ قيم الفضيلة والتضحية والوفاء. خصوصا المراقد المطهرة لآل البيت عليه السلام، وأبرزهن زيارة العاشر من محرم ذكرى استشهاد الحسين عليه السلام وكذلك زيارة الأربعين لمرقد الإمام الحسين عليه السلام. وتعد زيارة الأربعين من أكبر الزيارات وأهمها في تاريخ المسلمين وأتباع أهل البيت وكانت تسمى (زيارة الأنصار) وهي نسبة إلى أنصار الحسين وقد حث الأئمة على هذه الزيارة وإقامة شعائرها. فهي تأكيد دائم على الولاء للنهضة الحسينية وسيرتها الخالدة ورسالة واضحة إلى كل طغاة العامل وصرخة مدوية بوجه الظالمين والمستبدين وأن التواصل مع مبادئ الإمام الحسين عليه السلام- عقيدة ثابتة وراسخة في أذهان الأمة. إن التاريخ الإسلامي يحمل أجمل الصور وأبلغ الدروس والعبر، والتراث الإسلامي غني في شتى المجالات العلمية والاجتماعية والروحية والجهادية.. والملحمة الحسينية هي أبرز تلك المواقف والأحداث التي أثرت في المجتمع الإسلامي وحفظت الإسلام من الضياع ورسخت الهوية الإسلامية وكشفت زيف المتلبسين بلباس الإسلام والحق وعرت الباطل، الذي سقط بفعل الثورة والحركة التي جسدها الإمام الحسين عليه السلام في واقعة كربلاء. ولقد حاول كثير من الطغاة من بني أمية وبني العباس القضاء على هذه الملحمة وآثارها الكبيرة في نفوس المسلمين وغير المسلمين. الانفتاح على الإمام عليه السلام والحدث الحسيني من حيث هو نموذج عالي للقيم الإسلامية والإنسانية، ويمثل درجة عالية من الوعي السياسي والإسلامي والإنساني، لأنه استجاب للأمة التي كانت تعاني الظلم والفقر، والواقع المنحرف أيام الحاكم الأموي ولهذا أنطلق (إنما خرجت لطلب الإصلاح في أمة جدي). كان الإمام الحسين عليه السلام يعيش القضية بعقله وقلبه ومسؤوليته التاريخية وواجبه الإسلامي الملقى على عاتقه وبلغ أحساسه الإنساني بالمجتمع لذلك قال ((فمن قبلني بقبول الحق فالله أولى بقبول الحق)) ولذلك لم يدعو إلى زعامة وخلافة شخصية وإنما دعا إلى تأييد الحق المرتبط بالله. إن هذه الزيارة المليونية التي يتوجه الناس إليها صوب كربلاء لزيارة الإمام الحسين عليه السلام هي من أقوى الرسائل التي يبعثها عشاق الحسين إلى كل حاكم متسلط وطاغية قديما وحديثا.. Visits to holy sites occupy an important position in the personality of a religious person regardless of his/her religion and its impact is not limited to performing religious duties, but extends to the person’s relation to leaving “disliked” (makrouh) doings and performing “recommendable” (mustahabb) doings that have positive effects on a person’s consciousness, behavior and thinking. Hence, visiting Sacred sites and performing other recommendable doings tie the person closely with values of virtue, sacrifice, and loyalty leaving a profound impact on the entrenchment of those values in his/her character. These visits are specifically impactful when paid to the Sacred Shrines of the “Prophets’ Family” (Ahl Albeit) (peace be upon them) In particular, mainly Imam Al-Hussain’s (peace be upon him) Shrine on the tenth of Muharram and on The Fortieth Day after his martyrdom. The Fortieth Day Visit is considered one of the most important and largest visits in the history of Muslims and followers of (Ahl Albeit), and was called the "Al-Ansar Visit" (supporters’ visit) in reference to the supporters of Imam Al-Hussain (peace be upon him). Infallible Ahl Albeit Imams have always urged their followers to perform its rituals. This visit is a constant affirmation of loyalty to Imam Al-Hussain’s Rise against tyranny, and its immortal course, it is a clear message to all tyrants in the world, and a resounding cry in the face of oppressors and autocrats, stating that living by the principles of Imam Al-Hussein (peace be upon him) is a firm and entrenched faith in the minds of the nation. The Islamic history bears the most beautiful images, lessons, and morals, and the Islamic heritage is rich in various scientific, social, spiritual and jihadist fields…. The Real Epic of Imam Al-Hussain is the most prominent of those heroic events, it has affected the broad Islamic community, kept Islam from being lost, entrenched the Islamic identity, uncovered falsehood and revealed the truth of the insincere fake people who pretended to be Muslims. Imam Al Hussain’s (peace be upon him) revolution defeated falsehood through the real epic of Karbalaa’. However, many tyrants from Umayyad tribe (Bani Umayah) and Al-Abbas Tribe (Bani al-Abbas) have tried to eliminate the effect and course of this real epic, and tried to eliminate its significant effects on the consciousness of Muslims and non-Muslims at those times. Openness to the Imam (peace be upon him) and his real epic rise as a splendid model of Islamic and humanitarian values, represents a high degree of political, Islamic and humanitarian awareness, because the Imam moved and set off in response to the nation that was suffering from injustice and poverty, and the perverse conditions under the authority of Umayyad ruler. Imam Al-Hussain’s (peace be upon him) famous statement was (I moved and set off to demand reform in my Grandfather’s (peace be upon him) nation).
لتقول لهم نحن نرفضكم وقد فشلتم في القضاء علينا وقد انتصرت مبادئ الحسين لأنها من أجلنا وأصبح ملاذا لكل المؤمنين والأحرار من مختلف الأديان والملل والنحل، وهذه الزيارة باقية وتتمدد وتتوسع إلى يوم القيامة. لذلك تتطلب منا أن نجيب على أسئلة البحث الآتية: - الأصل الشرعي لزيارة الأربعين وتاريخها والروايات التي أكدتها. - تسليط الضوء على هذه الشعيرة وجذورها التاريخية وكيف تطورت؟ - الكشف عن حضور هذه الزيارة البارز في حياتنا الاجتماعية والدينية. - فوائدها الروحية والعقائدية والسياسية والاجتماعية والثقافية وأثارها الإيجابية. - توظيف هذه الشعيرة واستثمارها من أجل الإصلاح الاجتماعي والسياسي ومواجهة الفساد المالي والإداري. - المشي والبكاء والتشبيه (المسرح الحسيني) وتجسيد المعركة وأحداثها واستنباط العبرة منها. - تهذيب هذه الزيارة من المستجدات والبدع التي طرأت عليها وبعض السلوكيات الخاطئة المسيئة إلى قدسية الحدث الحسيني. Imam Al-Hussain (peace be upon him) was living the cause with his mind, heart, historical responsibility, and his Islamic obligation, and he conveyed his sense of humanity to the society, so he said “Who accepts me through accepting the right, then God is the First in accepting the right”, therefore he did not call for leadership and personal succession but called for support of the “right” associated with God. This multi million persons visit to Karbala, The Fortieth Day Visit of Imam Al Hussain is one of the strongest messages that Al-Hussain lovers send to every past and present domineering and tyrant ruler, telling those rulers we reject you and you have failed to eliminate us, Imam Al-Hussain’s (peace be upon him) principles have triumphed because they are for our sake and he with those principles have become a sanctuary for all believers and free humans of different religions, sects, and affiliations. This visit shall remain, extend, and expand to doomsday. We are therefore required to answer the following quests: - Explain the legitimate origin of The Fortieth Day Visit, its history and the sacred narrations that confirmed it. - How has this historical ritual evolved? Highlight this ritual and its historical roots. - Reveal the presence of this outstanding visit in our social and religious life. - Its spiritual, ideological, political, social and cultural benefits, and positive effects. - Utilize this ritual in social and political reform and in confronting financial and administrative corruption. - Marching, crying, and the analogy through acting the events of the battle (Imam Al-Hussain’s (peace be upon him) Theatre) to take them as moral lessons. - To refine the practices of this multi-million persons visit ensuring the removal of few novel fads and misconduct, and this to ensure nothing touches the sanctity of the blessed event
Keywords: آل البيت -- أبو طالب، الحسين بن علي، ت. 61 هـ. -- الوعي السياسي -- الإصلاح الإجتماعي